Effect of 3D Unit Cube Board Media on Students’ Understanding of the Concepts of the Volume of a Cube and a Rectangular Prism - Desi Ayu Lestari; Isrok'atun Isrok'atun; Aah Ahmad Syahid (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Elementary school students still struggle to understand the concepts of the volume of a cube and a rectangular prism due to the abstract nature of these concepts and the lack of concrete learning materials. This study aims to analyze the effect of 3D unit cube boards on students’ understanding of the concepts of the volume of a cube and a rectangular prism, the effect of conventional media in the form of instructional videos, and the differences in the effects between these two types of media. The study employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The sample consisted of 67 fourth-grade elementary school students in Cisitu Subdistrict, Sumedang Regency, comprising 30 students in the experimental class and 37 students in the control class. Data were collected using a conceptual understanding test consisting of 6 complex multiple-choice items and 8 essay items that measured students’ ability to interpret, provide examples, classify, summarize, conclude, compare, and explain the concept of volume. Data analysis was conducted using the Wilcoxon test, the Mann-Whitney test, and N-Gain analysis. The results of the Wilcoxon test showed that there was a significant increase in conceptual understanding in both the experimental and control classes (p = 0,000 < 0.05). The results of the Mann-Whitney test showed a significant difference in effect between the two groups (p = 0,002 < 0,05). The N-Gain analysis showed an average increase of 0,40 in the experimental class, which falls into the moderate category, while the control class showed an increase of 0,24, which falls into the low category. These findings indicate that the use of unit cube 3D board media results in a higher improvement in conceptual understanding compared to conventional media in the form of instructional videos. Therefore, unit cube 3D board media can be recommended as an alternative learning medium for teaching the volume of cubes and rectangular prisms in elementary school.